2000
DOI: 10.6009/jjrt.kj00001357329
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Patient's Dose Control Using an Area Exposure Product Meter

Abstract: 二 ed Aug . 2 , 2000 ; CDde Nos . 621 、 814 ゆ mommwwwwwwww ー pm . ww and measured entrance dc)ses , the deviation was about 10 % in phan − tom studies and 20 % in the clinical setting . Using our equation , calculation of entrance skin dose is pos − sible from area exposure product and is useful forpatient dose control in the clinical setting .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Data including age, gender, weight, body mass index (BMI), primary diagnosis, levels fused, cumulative fluoroscopic time, cumulative area dose product (DAP) and cumulative air kerma ( AK ) (obtained from the DAP monitor system originally installed on the fluoroscope), operating time, extra time required for this procedure, and complications related to screw placement were extracted from each patient’s medical record. To facilitate comparisons with other studies, the entrance skin dose (ESD) for each patient was calculated from the DAP and AK values using the following formula [ 27 , 28 , 29 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Data including age, gender, weight, body mass index (BMI), primary diagnosis, levels fused, cumulative fluoroscopic time, cumulative area dose product (DAP) and cumulative air kerma ( AK ) (obtained from the DAP monitor system originally installed on the fluoroscope), operating time, extra time required for this procedure, and complications related to screw placement were extracted from each patient’s medical record. To facilitate comparisons with other studies, the entrance skin dose (ESD) for each patient was calculated from the DAP and AK values using the following formula [ 27 , 28 , 29 ]. …”
Section: Methodsmentioning
confidence: 99%
“…2) However, neuroendovascular procedures frequently involve long fluoroscopic time, high-dose fluoroscopic mode, and greater numbers of exposure sessions, which increase radiation dosage for patients and operators, resulting in radiation injuries. [3][4][5][6][7] We previously reported that patient skin doses from neuroendovascular procedures are higher than those from abdominal and cardiac IR. 8) Specialized skills are required to safely perform neuroendovascular procedures, leading the radiation risk to increase to some particular operators.…”
Section: Introductionmentioning
confidence: 99%